APPLICATION OF THE HUMPTY DUMPTY FALLS SCALE (HDFS) RISK ASSESSMENT INSTRUMENT IN CHILDREN IN THE ASOKA WEST WARD OF Dr. SARDJITO GENERAL HOSPITAL, YOGYAKARTA - Adinda Cindy Paramita; Sumarti Endah Purnamaningsih Maria Margaretha (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2025)
Children are a vulnerable group at risk of falling during hospitalization due to underdeveloped motor and cognitive functions. Falls can lead to serious injuries, thus requiring accurate assessment and preventive measures. Objektive study aims to describe the application of the Humpty Dumpty Falls Scale (HDFS) for fall risk assessment in pediatric patients at the Asoka Barat Ward of RSUP Dr. Sardjito Yogyakarta. Method used was a descriptive case study involving nine pediatric patients, divided into two groups: with and without medical interventions (BMP/LP). Data were collected through observation, interviews, and documentation review. Results showed that the majority of patients were classified as high fall risk (score ≥12), especially in the group with BMP/LP interventions, where an increase in HDFS scores was noted after the procedures. Conclusion that HDFS is effective in identifying fall risks in children and can serve as a reference for appropriate nursing interventions